2020
DOI: 10.5296/ijele.v8i1.16358
|View full text |Cite
|
Sign up to set email alerts
|

Merging the E-journaling and the Workshop Methods to Reduce Prep-Year Students’ Writing Apprehension: An Experimental Study

Abstract: Preparatory (prep) year students presently encounter a significant disparity between prior to college English writing and the much superior level of competence needed for potential academic programs in Saudi Arabia. Study has verified the operational efficacy of the methods of e-journaling and writing workshop on alleviating writing apprehension but on a separate basis. This study represents an original contribution to knowledge through exploring the effects of merging these two outstanding methods. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Drastically, research conducted in several Arab states has revealed that college undergraduates struggle with significant difficulty in English in general and writing in particular (Alsamdani, 2010). Correspondingly, it is assumed that the problem of first-year undergraduates at the present study"s context which primarily lie in their dearth of confidence and lack of university-level writing skills could be tackled by a treatmentprogramme that integrates interactive e-journaling and communicative writer"s workshop techniques (Mohammed et al, 2020). This, we argue, could improve the participating students" writing skills.…”
Section: Statement Of the Problemmentioning
confidence: 90%
“…Drastically, research conducted in several Arab states has revealed that college undergraduates struggle with significant difficulty in English in general and writing in particular (Alsamdani, 2010). Correspondingly, it is assumed that the problem of first-year undergraduates at the present study"s context which primarily lie in their dearth of confidence and lack of university-level writing skills could be tackled by a treatmentprogramme that integrates interactive e-journaling and communicative writer"s workshop techniques (Mohammed et al, 2020). This, we argue, could improve the participating students" writing skills.…”
Section: Statement Of the Problemmentioning
confidence: 90%